Applications for Use in Music Teaching: Characterization and Description - Portela, Bruno Sergio (European Journal of Social Science Education and Research, 2023)
Educational technology has been constantly evolving, which can currently be found within the various types of cell phones, in order to assist in pedagogical practices. Thus, the present study aims to characterize and describe the applications available for use in teaching music theory in Basic Education. For that, a search was carried out with the term “musical theory”, with the segmentation of free applications, in an application store for cell phones. The results were then categorized by app name, available languages, purpose, file size, and user ratings within the app store. When carrying out the query, on the application access platform, 18 applications were found for teaching music theory. Most of the applications had the Portuguese language option, file sizes from 1 to 342.2 MB and evaluation grade variation from 1 to 5. As for the purposes, applications were found for specific teaching of instruments (guitar, piano and drums), sheet music reading, rhythm and melody teaching, in addition to auditory training. Therefore, the free applications found inside cell phones seem to be an excellent alternative to help teaching music theory to students within Basic Education.